Pendampingan Pengembangan Kemasan Produk bagi Pelaku IKM Kabupaten Aceh Besar melalui Pendekatan Product Development - Zahriatul Aini; Daudy Sukma; Desy Puspita; Khairita H; Rahmat Arfan (Universitas Muhammadiyah Palembang, 2026)
This community service program aims to enhance the capacity and competitiveness of Small and Medium Enterprises (SMEs) in Aceh Besar Regency through product packaging innovation assistance. The background of this activity is the significant potential of SMEs in Aceh which still faces serious challenges, especially in the aspects of packaging design, branding, and product legality such as halal and PIRT labels. The method used is a Product Development approach, which includes the stages of ideation, prototyping, and market validation. The program was implemented in August 2025 and involved 25 SME actors in the processed food and creative products sectors. The assistance was provided through theoretical and practical training sessions, including the use of simple graphic design applications like Canva. The results indicate improvement in participants' understanding, evidenced by an increase in the mean score from 62.4 in the pre-test to 84.1 in the post-test, representing a 35% growth. Furthermore, the program successfully produced new packaging prototypes that were validated by consumers, with results showing an increase in visual appeal (78%), clarity of information (82%), and consumer purchase intention (76%). Overall, this program not only improved the participants' knowledge and skills but also resulted in tangible innovations that can enhance the competitiveness of SME products in the broader market.